Titans. Vol. 3, Hard feelings - Layman, John, 1967- (DC Comics, 2025)
A league of their own! After the events of Absolute Power, the team looks towards the future and their place in it. Will their failure to control Amanda Waller mean lasting consequences for the hero community?